Research on the effects of free fatty acids dynamics of de-cored and non-de-cored unripe oil palm fresh fruit bunches / Muhammad Fakhrurrodhi Zainal Ashirin - Zainal Ashirin, Muhammad Fakhrurrodhi (Faculty of Plantation and Agrotechnology, 2018)
Harvesting the Unripe Fresh Fruit Bunches (FFB) has become a common problem by the plantation harvesters which can actually lead to lower Oil Extraction Rate (OER) at the palm oil mill. The Unripe FFBs are usually rejected at the mill and if processed it can lead to Un-stripped Fruit Bunches (USB). Consequently, the OER of FFBs at the mill would be affected. In this study, the Unripe FFBs were de-cored of their stalk using a special de-coring machine and its FFA dynamics was studied. De-coring is a method to remove the stalk of FFB so that steam penetration into the FFB would be improved and eventually will reduce the problem of USB. In this study, it was found that the FFA de-cored unripe FFB was higher than non-de-cored unripe FFB. The FFA profiles concentrations were analysed using two statistical methods; One Way-analysis of variance (ANOVA) and Pearson correlation coefficient test. ANOVA results showed FFA concentration profile for de-cored unripe FFBs was much significantly affected by the storage time than non-de-cored unripe FFBs. The Pearson correlation coefficient test on FFA concentration profiles over storage time for both de-cored (r = 0.983) and non-de-cored (r = 0.856) showed strong linear relationship. At the end, the economic analysis of this study was evaluated so that appropriate management recommendations could be provided to improve the overall palm oil mill performance.